Effects of injection molding gate mechanism on parameters machining and defects of book tray - Abdul Azwan, Abdol Zahar (2009)
Demand on plastics product in this country is very tremendous because plastic product has better quality, design and appearance than any material product. In order to produce better quality of plastics product, it needs to have some processes and most important is initially in design stages. The design has to be correct and can produce better product, so it needs to be analyzing before fabricate the mold. Material flow analysis should be running to the plastic product to ensure no defects and follow the characteristics from actual specification. The three-dimensional solid modelling of plastic product (book tray) was developed using the computer-aided drawing software. The dimension of product based on the actual product mould. The three-dimensional solid modelling of plastic product will import to the computer aided engineering software. The computer aided engineering software was then performed is using Moldflow simulation software. The computer aided engineering model of product was analyzed using injection flow analysis. The analysis need to do in three times for each gates mechanism. Finally, the best result of number of gates, gates locations, and sizes of head of gates obtained from the analysis. From filling times, the cycle time of product producing can be calculated for finding the best gates mechanism. The cycle time can relate to the production capacity, product cost and profit. From that comparison, the best gate mechanism for plastic product (book tray) can be selected and also can know the effect of parameters machining and defects of book tray. This project is using Moldflow Plastics Insight 5.0 software to analyze the effect of gate mechanism. Book tray has been chosen as subjects of experiment. Before get the best mechanism of the gate the analysis that should be analyze are number of gates, gate location, and gates sizes. By using this analysis method also can reduce the cost in define the gate mechanism for plastic product using manual method.